PARENTS INVOLVEMENT IN CHILDREN'S EDUCATION AT SD ISLAM AL-KAUTSAR KELURAHAN SIMPANG BARU KECAMATAN TAMPAN - Silfiani, Nova Silfiani; Bahar, Aswandi Bahar; ', Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is motivated lack of parental involvement in children's education in SD Islam Al-Kawthar Simpang Baru Village District of Tampan. The research problems are Is parental involvement in children's education in SD Islam Al-Kawthar village Baru Simpang sub-district Charming. The purpose of this study was to determine the involvement of parents in the education of children in elementary Islam Al-Kawthar Baru Simpang Village District of Handsome. The population in this study were 106 parents and samples of this study 31 parents with a critical level of 10%, the sample used is random sampling. Data collection instruments, namely a questionnaire with 109 statements and after the trial lived 85 valid statement to be made in the instrument of research. Data analysis through quantitative descriptive analysis. Presentation of the answers obtained from the calculation results based on the indicators of cognitive expressed a positive attitude adolescent negative 89.24% and 2.25%. While based on affective aspects declare a positive attitude adolescent negative 44.21% and 47.51%. Furthermore, it can be seen from the aspect conative stating positive attitude adolescent negative 43.67% and 47.63%.Keywords: Parent involvement, Children's Education